A new species of Arapona from Peru (Hemiptera: Cicadellidae: Iassinae: Gyponini) - Alexandre Cruz Domahovski; Rodney Ramiro Cavichioli (Zoologia (Curitiba), 2014)
Arapona furcata sp. nov. is described and illustrated based on a male specimen from Peru, department of Madre de Dios. This species can be recognized by the following features: 1) styles without a concavity on the ventral margin; 2) aedeagus robust and with a pair of long and slender preatrial processes; and 3) aedeagus with two apical processes, each with a sharp and hook-like apex. A key to the three known species of the genus is added.